If it's not what You are looking for type in the equation solver your own equation and let us solve it.
30(x-2)+5=22x-55+8x
We move all terms to the left:
30(x-2)+5-(22x-55+8x)=0
We add all the numbers together, and all the variables
30(x-2)-(30x-55)+5=0
We multiply parentheses
30x-(30x-55)-60+5=0
We get rid of parentheses
30x-30x+55-60+5=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 4x3+13=−734x3+13=-73 | | (x)=-3x+2 | | 170+40*26x=1200 | | X=40-1.25x | | -8=4(x-6)-8x | | (3/5)e-6=-(2/5)e-3 | | -4=-5/2c | | 6(7x+1)-5=23X+39+8x | | 4+2/5r=2 | | X/2+7x+90=180 | | 170+40/x=1200 | | (3/5)*e-6=-(2/5)e-3 | | 36^b-3=0 | | 60-3x=40+2 | | -4.41(b−19)=8.82 | | 4r+35(r^2+34)=0 | | 72=2x+10 | | 42-(2x+4)=4(x+6)+x | | 9z+4+28+31=180 | | 3(g+1)−5=4 | | (x+25)+(x•3)=435 | | -4(u-4)=8u+40 | | 4+6x=21 | | |5x+3|=|x+11| | | (3/5)*e-6=(-2/5)e-3 | | p+17.12=2.33 | | 70=10(j+2) | | (3/5)*e-6=-2/5e-3 | | -4(s+19)=-12 | | 4d-12=28 | | (3/5)*e-6=-2/5(e-10)-7 | | 5-2+x=2x-3 |